PERENCANAAN PARTISIPATIF PADA DINAS PEKERJAAN UMUM KOTA TANGERANG - Ronald Titon; Luki Karunia (Jurnal Good Governance, 2018)
This study aims to analyze the participatory planning process at the Tangerang City Public Works Agency. The method used in this study is descriptive with a qualitative approachThe focus of participatory planning analysis research based on participatory planning models includes aspects: Investigation, Problem Formulation, Identification of Carrying Capacity, Formulation of Objectives, Establishing Detailed Steps, and Designing a Budget. The sources used are primary data and secondary data. Data collection techniques with observation, interviews, and documentation. Data analysis method with data reduction, data presentation, and conclusion drawing.The results of the analysis show that the aspect of investigation starts from the level of RT / RW, Village Musrenbang, District Musrenbang up to the SKPD Forum. Aspect formulation of the problem found data collected is what is truly felt by the community, even though there are some of the data collected which is then used as an activity not felt in the expected year. The identification aspect appears to be carrying capacity. Aspects of formulating objectives have used the principles: Transparent, Responsive, Participatory, and Accountable. The aspect of setting detailed steps, the planning process carried out already contains what will be achieved, what activities will be carried out in accordance with the planning document and the proposed results of the Musrenbang, the division of tasks / responsibilities at the government level, especially the technical service the community level only proposes proposals for activities, and has included time even though it is still general. Community involvement should be carried out continuously. Government officials are expected to be resource persons and facilitators and mediators in the planning process. An information system is needed that specifically handles the planning process that can be accessed by the general public in order to see the proposals and the results of the planning process that has been implemented.Keywords: Partisipative Planning Process